UPAYA MENINGKATKAN HASIL BELAJAR SAINS DENGAN METODE DISKUSI PADA SISWA KELAS V SD NEGERI 011 BUKIT KAPUR - Zambri ' (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
This research was motivated by the low result of learning science class V students of SDNegeri 011 Bukit Kapur. This study aims to improve learning outcomes science class Vstudents of SD Negeri 011 Bukit Kapur by using the method of discussion. Subjects in thisstudy were students of class V SD Negeri 011 Bukit Kapur, totaling 35 students. This researchis a class act, carried out by two cycles. Parameter research is student learning outcomesconsisting of absorption, mastery learning, student learning activities and teaching activitiesof teachers. The results showed that in the first cycle the average value of daily tests is69.71% (Enough) and the second cycle of the average value of daily tests was 78% (Good).Mastery learning increased in the first cycle was 82.86% and the second cycle is 94.28%.Activities of students in the learning process increased from 73.98% (Enough) in the firstcycle to 73.09% (Enough) in the second cycle. Activities teachers in the learning process is92.5% (Very Good) in the first cycle and 96% (Very Good) in the second cycle. From theseresults it can be concluded that the discussion method can improve learning outcomes scienceclass V students of SD Negeri 011 Bukit Kapur.